Utilizing Communicative Grammar and Comic Strip Techniques to Assist Primary Students in Developing their Speaking Skills - Edy Suseno; Dian Novita; Fika Megawati (Saniya Institute, 2025)
Presenting concepts to elementary school pupils is crucial. It is to improve their capacity to exchange ideas with one another. Fifteen elementary school pupils in a public school encountered difficulties in accomplishing this objective. They voluntarily enrolled in a treatment class to deal with these shortcomings. The teacher began by teaching basic bilingual grammar using the book's supplied vocabulary. After finishing the lesson, the instructor invited the class to complete comic strip activities. They completed the assignments in small groups. They used speaking practice and peer teaching based on the discussed content to make the activity meaningful. To get the teacher's opinion, the pupils then displayed their text and audio creations on the screen. A qualitative analysis of the information acquired throughout the teaching and learning process was then conducted. It has been determined that comic strip techniques and communicative grammar aid in the improvement of primary pupils' speaking abilities. Teachers can use it to teach related subjects, which is beneficial. Additionally, it prompts other researchers to conduct more in-depth observations on similar topics.